Hyptis brevipes AND Paullinia pinnata EXTRACTS AND THEIR FRACTIONS PRESENTING ACTIVITY AGAINST Mycobacterium abscessus subsp. massiliense - das Neves, Rogério Coutinho; Gomes Andrade, Rayanny; Alexandre Carollo, Carlos; Galdi Boaretto, Amanda; Kipnis, Andre; Paula Junqueira- Kipnis, Ana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
Medicinal plants are of great interest for the discovery of new biomolecules with diversified effects. Over the last decade different outbreaks caused by Mycobacterium abscessus subsp. massiliense have been reported, evidencing it as an important emerging pathogen in underdeveloped countries. This study investigated the antimycobacterial activity of six Brazilian medicinal plant extracts and their fractions. Hyptis brevipes, Tocoyena formosa, Randia armata, Paullinia pinnata, Lafoensia pacari and Anadenanthera colubrina were evaluated against M. a. massiliense. Total extracts from the medicinal plants H. brevipes, T. formosa, P. pinnata and L. pacari presented a minimal bactericidal concentration of 1 mg/mL. After fractioning, the ethanolic fractions from H. brevipes and P. pinnata presented bactericidal activity, and the ethyl acetate fraction from H. brevipes and T. formosa presented antimycobacterial action. The best bactericidal function of all plant fractions was the ethanolic, which contained rutin and rosmarinic acid that were shown to have microbicidal activity. KEY WORDS: Mycobacterium abscessus; medicinal plants; Brazilian medicinal plants; HPLC and biodiversity.